The FEM Application in Numerical Analysis of Slewing Rings Roller/Ball Combination Bearing - Marek Krynke; Piotr Sygut (Communications - Scientific letters of the University of Zilina, 2017)
Slewing bearings are selected based on the characteristics of capacity, which determine the area of the permissible load of the bearing. This capacity of a bearing does not take into account the real operating conditions of a bearing. This implies a necessity to take into consideration all the factors having an influence on the bearing capacity during its determination. The way of determining of the static limiting load curves profiles (static capacity chart) of a double-row roller/ball combination slewing bearing is presented in this article. In the calculations, taking into account flexural-torsional flexibility of bearing rings, flexibility and number of bearing clamping bolts and the most important parameters of the contact zone of rolling elements with bearing raceways, is presented in the paper. Concluding results have been obtained in numerical way. Distribution of internal load, which is in individual rows of a bearing, is presented here. Basic problems of modelling the component unit of the slewing bearing are discussed. In calculating the profile, the initial clamp of the fixing bolt, flexible rings, flexible casing and variation of the contact angle bearing are allowed for. Particular attention is paid to modelling of elements that are equivalent for balls bearing. Obtained results are presented as graphs.